Financial Technology: MSME Capability To Connect In The Digital Ecosystem In The Field Of Finance (Case Study in Rokan Hilir Regency) - Mubarak, Husni (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2023)
This study aims to determine the financial knowledge capabilities of UMKM actors and digital payment systems that are often used by UMKM actors in Rokan hilir District in running their business. Data collection techniques were carried out using surveys and observations. The research population is all UMKM actors in Rokan hilir Regency. This study used a probability sampling design with a simple random sampling method of 238 people. Based on the results of the research that has been done, it can be concluded that there are still many UMKM actors who only have basic financial knowledge skills, which are 35%. UMKM actors use Mobile Banking the most to run their business, which is 78%, while the least is using SMS Banking at 7%.